2016
DOI: 10.1681/asn.2016020177
|View full text |Cite
|
Sign up to set email alerts
|

Of Inflammasomes and Alarmins: IL-1β and IL-1α in Kidney Disease

Abstract: Kidney injury implies danger signaling and a response by the immune system. The inflammasome is a central danger recognition platform that triggers local and systemic inflammation. In immune cells, inflammasome activation causes the release of mature IL-1b and of the alarmin IL-1a. Dying cells release IL-1a also, independently of the inflammasome. Both IL-1a and IL-1b ligate the same IL-1 receptor (IL-1R) that is present on nearly all cells inside and outside the kidney, further amplifying cytokine and chemoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
159
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(168 citation statements)
references
References 128 publications
4
159
0
5
Order By: Relevance
“…The correlation of inflammatory markers, such as C‐reactive protein (CRP) and interleukin‐6 (IL‐6), to the severity of both kidney and heart dysfunction suggests that inflammation may contribute to the pathogenesis of CKD in HF and provides rationale for identifying potential mediators of cardio‐renal inflammation. Based upon experimental animal and cellular models, we postulated that interleukin‐1 (IL‐1), a master regulator of the inflammatory response, could be one such mediator …”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation of inflammatory markers, such as C‐reactive protein (CRP) and interleukin‐6 (IL‐6), to the severity of both kidney and heart dysfunction suggests that inflammation may contribute to the pathogenesis of CKD in HF and provides rationale for identifying potential mediators of cardio‐renal inflammation. Based upon experimental animal and cellular models, we postulated that interleukin‐1 (IL‐1), a master regulator of the inflammatory response, could be one such mediator …”
Section: Fundingmentioning
confidence: 99%
“…Based upon experimental animal and cellular models, we postulated that interleukin-1 (IL-1), a master regulator of the inflammatory response, could be one such mediator. 4 In this post-hoc analysis of the REDHART study (n = 52), 5 we compared the antiinflammatory effects of 2 weeks of anakinra 100 mg daily or placebo within the subgroup who had estimated glomerular filtration rate (eGFR) between 30 and 60 mL/min/1.73 m 2 (n = 22, 42%). In brief, REDHART was a 2:1 randomized, double-blind, placebo-controlled clinical trial that compared placebo against 2 or 12 weeks of anakinra, recombinant human IL-1 receptor antagonist, in patients with systolic HF and CRP ≥ 2 mg/L who were enrolled within 2 weeks of discharge from HF hospitalization.…”
Section: Potential Role For Interleukin-1 In the Cardio-renal Syndromementioning
confidence: 99%
“…Interleukin‐1β plays an important role in the leukocytes infiltration of renal inflammation . We further examined IL‐1β production in UUO model.…”
Section: Resultsmentioning
confidence: 99%
“…Interleukin-1β plays an important role in the leukocytes infiltration of renal inflammation. 25 We further examined IL-1β production in UUO model. We found that the cleavage IL-1β protein, pro-IL-1β protein and IL-1β mRNA production were significantly higher in UUO group at Day 3 and Day7, compared with sham groups (Fig.…”
Section: Fluorofenidone Reduces the Level Of Cleavage Il-1β In Kidneymentioning
confidence: 99%
“…We also demonstrate that treatment of ibrutinib to mice fed a HFD attenuated the formation of the NLRP3 complex, and blocked the proteolytic cleavage of pro-caspase 1 to active caspase 1 in the diabetic kidney and liver. Similarly, caspase 1/11 knock out mice display reduced renal inflammation and improved renal function in models of diabetic nephropathy and lupus nephritis (54). A clinical trial with monoclonal anti-IL-1β IgG gevokizumab in type 2 diabetic kidney disease is ongoing (EudraCT2013-003610-41) suggesting that targeting this pathway could have therapeutic value.…”
Section: Discussionmentioning
confidence: 99%